Anionic mineral mixture prevents milk fever and improves farmer income: evidence from a randomized controlled trial - A G Adeeth Cariappa; B S Chandel; Gopal Sankhala; Veena Mani; Sendhil R; Anil Kumar Dixit; B S Meena (Agricultural Economics Research Review, 2023)
The incidence of milk fever, a calcium deficiency disorder in dairy animals, can be prevented by supplementing their feed with anionic mineral mixture (AMM). Using data from 200 dairy farms in Haryana, a state in India, and a randomized controlled design, we find that supplementing animal feed with AMM reduces the incidence of milk fever from 21% to 2%, improves milk yield by 14%, and farmer profit by 35%. The milk yield in India, and therefore the risk of milk fever, is growing; AMM can be an affordable way to prevent milk fever and improve returns.